IMPACT OF AMPK ACTIVATOR METFORMIN ON SPERM QUALITY - Mong Diep, Nguyen Thi; Blesbois, Elisabeth (Vietnam Journal of Biotechnology, 2018)
Semen cryopreservation allows crucial management of animal genetic diversity. However, the freeze-thaw process causes biochemical and physical alterations, impairing sperm energy-dependent functions. Currently, many chemicals are added to the media to enhance frozen-thawed sperm quality during artificial insemination. The aims of this study was to determine the effects of Metformin (Metf) on fresh chicken sperm motility and ability to perform acrosome reaction, and to evaluate Metf’s effects on the functions of cryopreserved sperm. Chicken semen was diluted and incubated at 35°C in media supplemented with or without different doses of 5’-AMP-Activated Protein Kinase (AMPK) activator, Metf (0,5 to 5 mM). We then looked for the concentration improving the most sperm quality to use it in the cryopreservation media used for chicken sperm. Our results show that 1 mM Metf is the concentration giving the best results regarding sperm quality. AMPKα phosphorylation, viability, acrosome reaction ability (AR), and various motility parameters, were negatively affected by the freeze-thaw process, and that Metf partially restored them. Sperm quality improved (mean increased by 23% for motility, by 10% for viability) as well as AMPKα phosphorylation (mean increased by 30%). Moreover, fluorescent intensity levels of phospho-AMPK were also stronger with Metf than in the control. These results show that the presence of Metf in fresh semen has a positive impact on the quality of sperm and helps reducing the gradual decline in sperm motility caused by cryopreservation by partially restoring several essential sperm functions, and thus leads to a better overall quality of cryopreserved sperm.